Consumption : A Sociological Analysis - Warde, Alan (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book critically reviews recent social scientific investigations of consumption, a controversial topic with moral overtones, and of popular public interest and political and economic significance. The author explores how consumption affects personal identity and social position, developing a sociological analysis using theories of practice to account for everyday consumption, its role in the social order, and its consequences for environmental sustainability. The book offers a controversial analysis which explains consumption not in terms of the purchasing of commodities but of the organization and coordination of daily practices. Consumption will be of interest to scholars and students of sociology, anthropology, geography, cultural studies, consumer research, business studies and social theory.- Resumé vydavatel
Keywords: individuální spotřeba -- sociální aspekty; sociologie spotřeby; spotřebitelské chování; consumption (economics) -- social aspects; sociology of consumption; consumer behavior; elektronické knihy; monografie; electronic books; monographs